A study on the phenomenon of Filipino women marrying foreigners from acquaintance to marriage - Bacayon, Christine Joy A.; Labong, Windel Lyn B. (2009)
This study is entitled "A Study on the Phenomenon of Filipino Women Marrying Foreigners: From Acquaintance to Marriage." This study aims to know the following: (1) the reasons of the Filipino woman for marrying a foreigner; (2) the different stages and processes that take place in their relationship which lead to marriage; (3) the different conflicts the couple encouraged in their marriage; and (4) the adjustment and coping styles of the couples in solving the conflicts of their marriage. This exploratory research utilized the interview method in gathering the necessary data of the study. A purposive sampling was used in selecting the 15 respondents. The 15 respondents hailed from the provinces of Biliran, Southern Leyte and Leyte specifically Dulag and Tacloban City. The researchers have found out that: (1) Majority of the respondents married their husband for economic reasons.The Filipino women knew that the foreigner could give her a better life as well as her family. Other reasons for their marriage are developed affection towards the partner, a father for her children, companionship, the foreigner's personality, compatibility and love. (2) The stages being studied was divided into four: acquaintance, courtship, engagement and marriage. Most of the respondents met their husband through friends and family referrals (60%). One unique feature of the foreign nationals and Filipino women's courtship stage was that it is a period of getting to know each other. Majority of the respondents have long distance relationship with their partner during the courtship period, therefore their line of communication were through emails, letters, telephone calls and internet with the use of webcams. The foreigners also gave gifts to the Filipina as a part of his courtship style. The respondents' engagement period was rather short. Majority of the respondents had a civil wedding (73.34%). (3) Unlike married couples of the same race, intermarried couples experience conflicts in their different values and traditions which affect the initial part of their married life. One source of conflict is the difference in the concept of hospitability between the Filipina and her husband. The issue of money also matters among the couples. The existence of "tsismis" in the Filipino culture also caused trouble. Some foreigners did not like other people minding other's business. Lastly, the question of being honest and open with each other like any other couple also brought conflict. (4) The intermarriage couple resolves their conflicts by discussing the problem and compromising. Some respondents resort to displacement (throwing of things) when having a fight with their husband to release the anger and tension they felt. While others prefer to leave the issue behind and let time heal their problem. With the results mentioned, the researchers would like to recommend the following: (1) Some Filipino women seek the use of internet to find a potential foreign husband that is why implemented rules and regulations as well as laws formulated by authorities regarding the use of internet should be reviewed further and be strictly enforced to the affected and concerned persons. (2) Because Filipino women who married foreigners often experience culture shock at the initial part of the marriage, the conduct of counseling before and even during duration of the marriage should be administered to aid the gap and even during duration of the marriage should be administered to aid the gap and resolve conflicts caused by their cultural and personality differences. (3) Lastly, more researches and studies should be conducted about intermarriages particularly in the Filipino context since it has become a common phenomenon.